General chemistry 1 - Apodaca, Dahlia C. (Makati City : Diwa Learning Systems, Inc., 2020)
"This textbook is an assembly of updated, thorough discussions of significant, real-world chemistry concepts and principles, partly emanating from the author's experience as a practicing chemist. It is divided into two units. Each unit is composed of modules with exercises that allow both students and teachers to be exposed to important and socially relevant applications of chemistry. This weaves key principles of chemistry t4o various disciplines, allied or non-allied, in pursuit of technological and innovative developments."
Includes bibliography.
English text.
Keywords: Chemistry